Characterization of viral infections in children with influenza-like-illness during December 2018–January 2019 - Chao, Shuang; Wang, Yuejiao; Wu, Baolei; Li, Runqing; Dong, Jingxiao; Ji, Lina; Li, Xuejun; Li, Ran; Yin, Xiaomei; Zhao, Xiuying; Liang, Wannian (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Respiratory viral infection (RVI) is of very concern after the outbreak of COVID-19, especially in pediatric departments. Learning pathogen spectrum of RVI in children previous the epidemic of COVID-19 could provide another perspective for understanding RVI under current situation and help to prepare for the post COVID-19 infection control. Methods A nucleic acid sequence-based amplification (NASBA) assay, with 19 pairs of primers targeting various respiratory viruses, was used for multi-pathogen screening of viral infections in children presenting influenza-like illness (ILI) symptoms. Children with ILI at the outpatient department of Beijing Tsinghua Changgung Hospital during the influenza epidemic from 12/2018 to 01/2019 were included. Throat swabs were obtained for both the influenza rapid diagnostic test (IRDT) based on the colloidal gold immunochromatographic assay and the NASBA assay, targeting various respiratory viruses with an integrated chip technology. Results and discussion Of 519 patients, 430 (82.9%) were positive in the NASBA assay. The predominant viral pathogens were influenza A H1N1 pdm1/2009 (pH1N1) (48.4%) and influenza A (H3N2) (18.1%), followed by human metapneumovirus (hMPV) (8.8%) and respiratory syncytial virus (RSV) (6.1%). Of the 320 cases identified with influenza A by NASBA, only 128 (40.0%) were positive in the IRDT. The IRDT missed pH1N1 significantly more frequently than A (H3N2) (P<0.01). Influenza A pH1N1 and A (H3N2) were the major pathogens in <6 years and 6-15 years old individuals respectively (P<0.05). In summary, influenza viruses were the major pathogens in children with ILI during the 2018-2019 winter influenza epidemic, while hMPV and RSV were non-negligible. The coexistence of multiple pathogen leading to respiratory infections is the normalcy in winter ILI cases.